Nadzwyczajne podatki majątkowe - Kędrzyński, Adam (Wydawnictwo Uniwersytetu Łódzkiego, 2026)
The aim of this work was to check whether extraordinary taxes are just and meaningful. Case study, data analysis and text analysis (legal comparative methods, humanistic text reconstructions methods) methods were applied._x000D_ The conclusion from this research is that the paradigms of fundamental theories of justice are just way too different to allow us to draw clear conclusions, based on them alone. We need to provide rich empirical analysis and use theory as a supplementary resource._x000D_ In particular, the rarely discussed Turkish case is a proof of the possibility of an occurrence of an extremely unfair levy in the tax system, regardless of the applied theory of justice. Concerning the „efficiency” hypotheses, Western European examples from the interwar period are consistent with previous studies, which concluded that extraordinary taxes have little to no fiscal significance, only a short-term deflationary effect, a symbolic impact on reducing public debt, and only negative behavioural effects (increased tax avoidance, discriminatory behaviours based on religion, nationality and ethnicity in Turkish case). CEE cases, on the other hand, give some hope that extraordinary one-off wealth taxes might work if we lower our expectations towards them, and their marginal rates.